(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objectives: To study the biochemical status and screening of microvascular complications of type-1 diabetic patients. Study design and settings: It was a descriptive study carried out at Diabetic Clinic of PMRC Research Centre, FJMC, Lahore. Patients and Methods: Eight years case records of type-1 diabetic patients seen at the PMRC Research Centre FJMC Lahore from 1999-2006 were reviewed Out of 1265 diabetic patients sixty five were known type-1 diabetic. A 12 hours fasting blood sample was collected from each patient for serum total cholesterol , triglycerides , low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, urea, creatinine, uric acid and glucose as well as glycosylated hemoglobin (HbA1c) by using standard methods performed at Biochemistry laboratory of the research centre. Body mass index (BMI) was calculated. HbA1c<6.1 was considered as poor glycemic control. Relevant information of all patients was recorded with the help of a pre-designed proforma. They were also investigated for type-1 diabetic complications. Data was analyzed by using statistical software SPSS-15. Results: Sixty five type-1 diabetic patients mean age of 36±12.5 years of both sexes were screened. These patients were mostly illiterate or having primary education and poor family background and has family history of CHD, diabetes mellitus, hypertension, stroke and gout. Glycemic status (blood glucose level ≥11.1 mmol/l ) was noted in 10.8% and mean level of HDL-cholesterol was 0.95 ± 0.09 mmol/l. Rate of complications of reproductive, skin and gastrointestinal tract infection was higher in these patients i.e. 20%, 13.8%, and 10.8% respectively. Conclusion: The study indicates the prevalence of microvascular complications which were common in our type-1 diabetic patients and low HDL-cholesterol was a commonly associated condition among them, while duration of diabetes has significant association with retinopathy and respiratory complications.